A study of factive assertives in political speeches by u.s. president barack obama - Ngô,Đình Lộc; Ngũ Thiện Hùng (ĐHĐN : ĐHĐN., 2015)
The research in this paper examines the syntactic, semantic and pragmatic features of factive assertives in political speeches by U.S. President Barack Obama and identifies his strategies of using factive assertives. This research is a qualitative study based on the framework of speech act, epistemic modality and appraisal theory. It was carried out as a descriptive analysis. The corpus of 713 samples gathered from 50 most recent and well-known speeches was employed to investigate the syntactic, semantic and pragmatic characteristics of factive assertives in expressing the speaker’s assertion to the truth value of proposition. Appraisal theory by Martin & White (2005) is the theoretical framework for analyzing sematic and pragmatic features. Consequently, Obama’s patterns of using factive assertive were identified and summarize into general strategies. Syntactic characteristics discussed in this paper mentions the tenses and structural position of factive complements, sequences of tenses, the structure and properties of factive complements and the phenomena of complementizer deletion. Semantic and pragmatic features are classified and analyzed based on a main resource of appraisal theory, Engagement. The most significant finding of the study, the strategies of using factive asserives, are presented. The study finds out that Barack Omaba has a clear purposes when using each type of factive assertive predicates. Finally, some suggestions to improving oratory drawn from the findings are proposed to help English speakers use factive assertives effectively in speechmaking.
Keywords: factive assertives in political speeches by u.s. president barack obama; factive assertives in political speeches -- president barack obama